STRUGGLE FOR GETTING A POPULARITY IN TINA'S MEAN GIRL MOVIE (2004): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - KHUMAIROH, DIAN SEPTINA (2010)
This research investigates how struggle for getting a popularity. The major character is Cady Heron, the psychological development of major character in Tina's Mean Girl, is viewed by individual psychological approach. Therefore, the study analyzes the movie in terms or its structural elements and based on the individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses two data sources, they are: primary data source and secondary data source. The primary data source and object of the study, is the movie of Mean Girl itself. Meanwhile the secondary data sources are any books of literature and psychology, related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. The result of the analysis shows the following conclusions: first, Tina Fey wants to utter her idea that struggle for getting a popularity should be achieved by sacrifice, and second, struggle for getting popularity achieved by sacrifice will influence the psychological development of the major character. In this movie, Cady Heron as the major character has to struggle for getting popularity, to reinforce her psychological development.